Documenting Events in Times of Crisis: Investigating Traditional and Contemporary Thai Archival Practices - Sucha-xaya, Naya (Archivaria, 2022)
Traditional Thai archival practice, which consists of documenting events and ceremonies, can be traced to the activities of royal scribes in past centuries. Today, this practice is carried out by national archivists, far removed from people’s daily lives. However, current digital transformations and participatory, networked culture are making documentation more relevant now than in the past – and to virtually everyone.Focusing on records from times of historic emergencies, this article aims to understand Thai documentation behaviour from a socio-cultural perspective, with an eye toward considering how to adjust traditional archival practice to the contemporary Thai context. Archival sources documenting two crises – the Franco-Siamese military conflict of 1893 and a catastrophic tropical storm in southern Thailand in 1962 – are compared with new social media–based documentation consisting of posts, comments, and other activity during the cave rescue incident in northern Thailand in 2018. This comparison is complemented by insights from national archivists and other documentation experts regarding their experiences and their thoughts on the future of Thai archival practice.Together, this comparison and these insights show that Thai documentation retained some of its original principles and functions in Thai society when it moved into a digital landscape, but there is still room for it to become more engaging and, in some ways, better suited to common understandings of archives as a “hall of fame.” This article suggests that Thai archivists should embrace a participatory archives model in which professional archivists remain essential but shift their focus from recording and guarding information to fostering the reliability and sustainability of documentation.